(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article explores the types of sensations, focusing primarily on the linguistic expression of interceptive sensations. The interceptive process is characterized not only by the presence of a physiological signal but also by its reflection in consciousness and subsequent semantic processing. Although sensations arising within the internal environment of the body have a biological nature, their conceptual content is formed through human cognitive and sociocultural experience. To gain a deep understanding of the sociocultural and psychological factors of interoception, it is essential to study how a person verbalizes internal bodily sensations.